Hepatocyte depletion of ERK5 impairs the response to lipotoxic oxidative stress resulting in defective insulin receptor signaling. (March 2023) - Menconi, A.; Di Maira, G.; Lori, G.; Piombanti, B.; Navari, N.; Taddei, M.L.; Petta, S.; Pipitone, R.; Grimaudo, S.; Campani, C.; Tournier, C.; Rovida, E.; et al.
Abstract : Background/aims: Insulin resistance is an early event in nonalcoholic fatty liver disease (NAFLD), but the molecular mechanisms underlying the reduced response to insulin are still elusive. The mitogen-activated protein kinase ERK5 has been implicated in the development of hepatic fibrosis and cancer. Aim of this study was to investigate the role of ERK5 in the regulation of hepatocyte sensitivity to insulin. Methods: A murine hepatocyte cell line (MMH) was silenced using lentiviral vectors encoding shRNA for the ERK5 gene. Mitochondrial depolarization was assayed using the TMRE staining protocol. OXPHOS was measured by Seahorse. Mice with hepatocyte-specific deletion of ERK5 (ERK5ΔHep) were fed with a high-fat diet (HFD) for 16 weeks. For Glucose and insulin tolerance tests were conducted injecting 1 g/kg BW glucose or 0.8 U/kg BW insulin, respectively, i.p. Results: MMH stably silenced for ERK5 showed reduced Akt activation following insulin stimulation. When ERK5-silenced cells were exposed to palmitic acid and then stimulated with insulin, Akt activation was abrogated, and expression of the insulin receptor (IR) reduced. Additionally, ERK5 silencing induced phosphorylation and activation of JNK, resulting in phosphorylation of IRS-1 on inhibitory residues (S307). In parallel, an increase of mitochondrial ROS generation was observed in ERK5-depleted MMH. ERK5 is known to induce a NRF2-dependent anti-oxidative stress response. Expression of the NRF2-target genes HMOX1 and NQO1 was reduced in ERK5-silenced MMH. Treatment with NAC, a free-radical scavenger, prevented the downregulation of the IR and the increase in IRS1 phosphorylation on S307. Measurement of the mitochondrial membrane potential indicated a strong depolarization in ERK5-silenced cells, together with an impairment of mitochondrial OXPHOS, associated with up-regulated expression of PGC-1alpha and TRIB3, a negative regulator of insulin signalling through inhibition of Akt. ERK5ΔHep mice exhibited impaired glucose tolerance and reduced insulin sensitivity. Hepatocyte depletion of ERK5 in vivo was also associated with reduced expression of IR, and increased expression of PGC-1α and TRIB3 Conclusion: We have elucidated a new role of ERK5 in maintaining hepatocyte insulin sensitivity, via an antioxidant response involving IRS-1, PGC-1α, and TRIB3, and converging on Akt activation.